THE CENTRAL BANK OF BRAZIL AS AN AGENT OF INTERNATIONAL RELATIONS - Salvo, Mauro (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The paper has the objective to distinguish the Central Bank of Brazil as an agent of the International Relations and to state that its actions, internal or external, have some political connotation due to the impossibility to disconnect the economic from the political. The paper also intends to demonstrate that democratization, globalization and the awareness of the need to increase the transparency of the financial, economic and political relations, besides the increase of the international cooperation, strenghtened both the international and domestic institutions or increased the urge for countries that wish to insert themselves globally to develop strong institutions, among them their respective central banks.